(untitled) - Gad-el-Hak, Mohamed (Boca Raton, 2002)
The revolution is well underway. Our understanding and utilization of microelectromechanical systems (MEMS) are growing at an explosive rate with a worldwide market approaching billions of dollars. In time, microdevices will fill the niches of our lives as pervasively as electronics do right now. But if these miniature devices are to fulfill their mammoth potential, today's engineers need a thorough grounding in the underlying physics, modeling techniques, fabrication methods, and materials of MEMS.The MEMS Handbook delivers all of this and more. Its team of authors-unsurpassed in their experience and standing in the scientific community- explore various aspects of MEMS: their design, fabrication, and applications as well as the physical modeling of their operations. Designed for maximum readability without compromising rigor, it provides a current and essential overview of this fledgling discipline.
Keywords: Mechanical engineering; Handbooks, manuals, etc